2009
DOI: 10.1186/1471-2458-9-373
|View full text |Cite
|
Sign up to set email alerts
|

Sexual practices among unmarried adolescents in Tanzania

Abstract: BackgroundSexual activities are increasingly changing from the cultural point of view what they used to be. Knowledge of these practices among adolescents may be a basis to create awareness among adolescents on practices that involve risks. This study aims to assess sexual practices among unmarried adolescents in Tanzania.MethodsA cross-sectional survey was conducted among in-school and out-of-school but unmarried adolescents aged 10 to 19 in five locations in Tanzania. A questionnaire was used to collect info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 25 publications
5
64
1
Order By: Relevance
“…Rape may be under-reported in this study probably because it is considered shameful and hence remains secrete [22]. Another study done by Kazaura et al, revealed that 12.2% of unmarried adolescents reported rape as reason for the first sex [3]. It is possible that if the stigma attached to rape is removed, many more victims may likely report it and the perpetrators punished.…”
Section: Citation: Chihurumnanya a Lawrence Uo Benedict Na Uche Dmentioning
confidence: 84%
See 1 more Smart Citation
“…Rape may be under-reported in this study probably because it is considered shameful and hence remains secrete [22]. Another study done by Kazaura et al, revealed that 12.2% of unmarried adolescents reported rape as reason for the first sex [3]. It is possible that if the stigma attached to rape is removed, many more victims may likely report it and the perpetrators punished.…”
Section: Citation: Chihurumnanya a Lawrence Uo Benedict Na Uche Dmentioning
confidence: 84%
“…In India, HIV prevention efforts among the young are on the increase because it has been shown that about 21.7% of males and 6.3% of females become sexually active before marriage [2]. Elsewhere in Africa, the prevalence of premarital sex was found to be 32% among the young [3]. In 2008, 20% of women in Nigeria were already sexually active by age 15, and the median age for first sex stood at 17.7 years for women and 20.6 years for men [4].…”
Section: Introductionmentioning
confidence: 99%
“…Also, comparative studies of the group have shown disparities. A study done in Tanzania and Ghana revealed that in-school adolescents initiated sex at lower age than the out-of-school adolescents and had lower contraceptive use [3] [6]. In contrast, a similar study carried out in Uganda reported that in-school adolescents had initiated sex at a later age and had higher contraceptive use than out-of-school adolescents [4].…”
Section: Introductionmentioning
confidence: 87%
“…This might not be unconnected to the HIV/AIDS epidemic that is again common among this population. Previously, because of cultural and religious factors, [22] it is difficult to openly discuss and even teach youths sex education. The publicity campaigns on HIV/AIDS prevention have opened a window of opportunity to also discuss other sexually transmitted infections.…”
Section: Discussionmentioning
confidence: 99%